Prediction of optical coherence tomography-detected calcified nodules using coronary computed tomography angiography - Junichi Sugiura; Makoto Watanabe; Saki Nobuta; Akihiko Okamura; Atsushi Kyodo; Takuya Nakamura; Kazutaka Nogi; Satomi Ishihara; Yukihiro Hashimoto; Tomoya Ueda; Ayako Seno; Kenji Onoue; et al. (Scientific Reports, 2022)
Abstract Diagnosis of calcified nodules (CNs) is critical in the proper management of coronary artery disease, but CNs can be detected only using intracoronary imaging modalities. This study aimed to investigate the ability of coronary computed tomography angiography (CCTA) in predicting CNs detected using optical coherence tomography (OCT). From 138 patients who underwent OCT-guided percutaneous coronary intervention (PCI) after CCTA evaluation, 141 PCI target vessels were retrospectively enrolled and classified into CN (12 vessels/11 patients; CNs in the PCI culprit lesion) and non-CN (129 vessels/127 patients; without CNs) groups based on the OCT analysis. Retrospective CCTA analysis revealed significantly higher coronary artery calcification score (CACS), calcified plaque volume (CPV), and maximum calcified plaque area (MCPA) of the target vessel in the CN group than in the non-CN group. Receiver operating characteristic curve indicated that CACS ≥ 162 (area under the ROC curve (AUC 0.76, sensitivity 83.3%, specificity 54.2%), CPV ≥ 20.1 mm3 (AUC 0.83, sensitivity 100%, specificity 57.3%), and MCPA ≥ 4.51 mm2 (AUC 0.87, sensitivity 91.7%, specificity 78.3%) were the best cutoff values for predicting CNs. MCPA showed the highest AUC among all the CCTA parameters. In conclusion, CCTA is useful for predicting OCT-detected CNs in PCI target vessels.